جدوى تحول الشركات الصناعية العامة إلى التمويل الذاتي في العراق للمدة 2011-2018 - جلوب، دعاء عبدالحسين; العاني، ثائر محمود رشيد (جامعة تكريت - كلية الإدارة والاقتصاد, 2020)
The research aims to shed light on the industrial companies in Iraq and evaluate the transformation experience of one of the industrial companies that have moved towards self-financing, as most industrial companies suffer from large material losses and these losses are borne by the Ministry of Finance, which is a great financial burden on it at the time the state seeks to Directing their resources to economic development, and that industrial companies are still far from self-financing the same way as other industrial companies that have headed the same direction, and the importance of making radical changes in industrial companies by increasing their organizational efficiency and competitiveness.
يهدف البحث إلى تسليط الضوء على الشركات الصناعية في العراق وتقييم تجربة التحول لإحدى الشركات الصناعية التي اتجهت نحو التمويل الذاتي، ذلك أن معظم الشركات الصناعية تعاني من خسائر مادية كبيرة وهذا الخسائر تتحملها وزارة المالية التي يكون عبء مالي كبير عليها في الوقت التي تسعى فيه الدولة إلى توجيه مواردها للتنمية الاقتصادية، وأن الشركات الصناعية مازالت بعيدة عن التمويل الذاتي أسوا بالشركات الصناعية الأخرى التي اتجهت نفس الاتجاه، وأهمية إجراء تغيرات جذرية في الشركات الصناعية بزيادة كفاءتها التنظيمية وقدرتها التنافسية.
Keywords: الشركات الصناعية -- التمويل الذاتي -- الاقتصاد العراقي -- التنمية المستدامة